A reaction-based ratiometric fluorescent sensor for the detection of Hg(II) ions in both cells and bacteria - Pan, Sheng-Lin; Li, Kun; Li, Ling-Ling; Li, Meng-Yang; Shi, Lei; Liu, Yan-Hong; Yu, Xiao-Qi (Chemical communications (Cambridge, England), 2018)
A novel reaction-based fluorescent probe (ATC-Hg) was designed and synthesized via the "covalent assembly" principle, which exhibited excellent selectivity and high sensitivity for Hg2+ and (CHHg+)-Hg-3 Moreover, it is the first Hg(II) sensitive fluorescent probe that has been successfully applied in imaging in both cells and Escherichia coli.